THE SMALL MAMMALS (INSECTIVORES, BATS AND RODENTS) FROM THE HOLOCENE ARCHAEOLOGICAL SITE OF VALLONE INFERNO (SCILLATO, LOWER IMERA VALLEY, NORTHWESTERN SICILY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
The Vallone Inferno rock-shelter is an archeological site located at 770 m a.s.l. in the Madonie massif in Sicily. This massif is modeled into the Triassic and Oligocene sedimentary rocks of the Imerese Basin. Thearchaeological excavations conducted since 2008 have provided a long prehistoric and historic sequence from the Neolithic to the medieval period. From the four sedimentary complexes identified, only levels 3.4 to 3.1 from complex 3 and 4.2 from complex 4 have yielded small-mammal material. Level 4.2 is poor in remains and as yet without cultural ascription, though it has a radiocarbon age of 9450±50 years BP. Level 3.4 has yielded fragments of ceramic characteristic of the Middle Neolithic-Bronze Age period, with a radiocarbon age between 3948±35 and3244±42 years BP. Levels 3.3 to 3.1 have provided ceramic fragments ascribed to the Late Roman-Byzantine period, with a radiocarbon age between1332±26 and 1260±34 years BP.The small-mammal assemblages recovered from the sieving-washing of all the sediment from the excavation campaigns include a total of at least 14 taxa (three insectivores, four chiropterans and seven rodents). The materials from this locality provide the first mention in the fossil record of Sicily for Suncus etruscus, Muscardinus avellanarius, Eliomys quercinus and Rattus norvegicus, as well as the last occurrence for Arvicola amphibius. The scarcity of the remains recovered from stratigraphic levels 3.1, 3.2, 3.3 and 4.2 makes it difficult to undertake a palaeoenvironmental and palaeoclimatical interpretation of them. However, the richness in small mammal contents from level 3.4 allow us to show that this level is dominated by dry meadows and woodland areas with a temperature and precipitation range that lies within the current values for the surrounding area, coinciding with the dry and temperate phase detected previously by marine surveys and pollen and microcharcoal studies.
Keywords: Micromammals; biostratigraphy; palaeogeography; palaeoenvrionment; palaeoclimate; Middle Neolithic-Early Bronze Age; Late Roman-Byzantine period